A Preliminary Study: Treatment Outcome of Acute ST-Segment Elevation Myocardial Infarction with Streptokinase Infusion after Using Fast-Track Protocol in Pathum Thani Hospital - Sinsatienporn, Somsak (Journal of Health Science of Thailand, 2017)
Acute ST-Segment Elevation Myocardial Infarction (STEMI) is an important leading cause of morbidity and mortality inThailand. In the hospitals which lack cardiologists, fibrinolytic treatment should be performed as soon as possible (ฃ 60 minutes) to reduce cardiac death and subsequent adverse events, if there are no contraindications. The objectives of this preliminary study were to find out the efficacy, in-hospital morbidity and mortality rates (MR) and related factors of ิFast-Track Protocolี of treatment of STEMI with Streptokinase(SK) infusion within 60 minutes after arriving at the hospital which was newly launched in Pathum Thani hospital. In a retrospective study from 2 June 2006 to 8 January 2007 there were 36 patients with STEMI ranged from 38 to 90 years of age (mean 62, SD 14 years). Of which, 26 patients (72.2%) were male. Only 30 patients (83.3%, 21 males, 9 females) could undergo SK infusion (SK group), leaving out 6 patients (5 males, 1 females) with contraindications(Non-SK group). The risk factors for STEMI were hypertension (HT) 47.2percent, smoking 38.9percent, diabetes mellitus (DM) 30.6percent, dyslipidemia (DLP) 25.0 percent, family history of ischemic heart disease (FH)2.8percent, and patients with ณ 3 risk factors 16.7 percent. The MR of total 36 patients was 19.4percent (7/36cases), while MR of the SK group was 16.7percent (5/30 cases), much less than MR of the Non-SK group of 2/6 cases, and less than 22.1percent of MR of the Non-SK patients reported 3 years prior to this study(there were no using of SK at that time). Of the SK group, the Door-To-Needle (DTN) times were 22-335 minutes (mean 105,SD 76minutes, median 71 minutes). Only 10 patients (33.3%) had DTN times ฃ60 minutes as targeted and had the lowest MR (10.0%). Cardiogenic shock and congestive heart failure (CHF) were the main causes of death. Adverse effects of SK were bradycardia (30.0%), shock (26.7%), nausea and vomiting (20.0%),and minor bleeding (13.3%). Most of these complications were improved by supportive treatment. This preliminary study showed that SK infusion could reduce MR of STEMI patients. Further study on this method of treatment in a larger group of STEMI patients is needed for more reliable results.